(untitled) (Foro de Educacion, 2021)
Throughout the years, our western culture has moved away from the issue of death through its avoidance or even denial, removing it little by little from our environment. Therefore, we believe that an educational intervention with elders is necessary to eliminate the subject of death as a taboo, and to refer to it as part of our life and that as such it must arrive without having to suffer when we think about it. This article shows the story of older people about both positive and negative attitudes toward their own and others’ finitude, highlighting the importance and need to create various points of encounter and educational reflection, for example, in the Classroom Permanent Open Training. To do this, a qualitative methodological design was selected using semi-structured and in-depth interviews as information collection techniques. The results indicate a predominantly positive attitude of own death but not so much of the death of others, relating the fear or anxiety towards the finitude of a loved one. They explain their bewilderment when talking about finitude but claim to have it very present in their day to day because it is a topic very relevant to their age. We show the importance of creating educational spaces aimed at older people in order to treat these negative attitudes and reinforce positive ones. The purpose of a death education is for education professionals to base and reflect on their teaching, learning and unlearning and relearning in self-training where death takes its natural place.